PENYELESAIAN SENGKETA TANAH ULAYAT KAUM OLEH MASYARAKAT ADAT DI NAGARI SUPAYANG KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR (SENGKETA TANAH KAUM DATUK TIANSO DAN KAUM DATUK CUMANO) - Randy Prasetya; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The Republic of Indonesia is the State of Agriculture, the composition of the life of the people including the economy derived from the agriculture. As an agricultural country, of course the land problem is needed because of places of farming and gardening, as well as places of business, residence and also burial ground. If we discuss the land issue in West Sumatra, we can not help but worry about the Minangkabau Customary Law because the land is an inseparable part of the law itself.Inter-communal land dispute between peoples also experienced by indigenous peoples in Nagari Supayang Salimpaung Subdistrict Tanah Datarpersengketaan Regency is the struggle of treasure treasure that is the land of the house which resulted to the quarrel between the Datuk Cumano (Parikcancang Piliang) and Datuk Tianso (Suku Salo Caniago). This dispute that once stood a house, and the house was formerly controlled by Anwar Zen and his wife Liana, Anwar is a people of Datuk Rajo Penghulu Perak of Salo Caniago tribe, and Liana is a people of Datuk Cumano from tribe Parik cancan PiliangFirst, the purpose of the researcher is to write this thesis to find out the cause of the land disputes of ulayat by indigenous peoples in nagari supayang Salimpaung Subdistrict of Tanah Datar (case study of land dispute of Datuk Tianso and Datuk Cumano), How is the process of settling land disputes of customary land by indigenous peoples in nagari supayang Salimpaung District Tanah Datar (case study of land dispute of Datuk Tianso and Datuk CumanThis type of research can be classified in the type of sociological research, because in this study the authors directly conduct research on the location or place under study in order to provide a comprehensive and clear picture of the problem.This research was conducted in Tanah Datar regency of West Sumatera Province, while population and sample were all parties related to the problem studied in this research. Data sources use primary data, secondary data, and tertiary data. In addition, the method of data collection in this study is to question through, interview and literature study. Suggestions should be given is expected to the head of the community / penghulu to further deepen the customs of Minangkabau especially in the settlement of the communal land disputes of the people because customary law is a law that lives in indigenous peoples and it is highly appreciated from the descend, in order to create peace between indigenous peoples in the Minangkabau.Keyword: Dispute Resolution - Culture - Hak Ulayat